Blastopsylla occidentalis Taylor (Hemiptera: Psyllidae), a new introduced eucalypt pest in Chile - Burckhardt, D.=700 1 Elgueta, M.
(Es, En)
Ilus., 8 ref.
Keywords: HEMIPTERA; PSYLLIDAE; PLAGAS DE PLANTAS; EUCALYTUS; TAXONOMIA; DISTRIBUCION GEOGRAFICA; CHILE; REVISTA CHILENA DE ENTOMOLOGIA